Bringing Housing Education Home to First Nations in Canada: York Factory First Nation Transforms Housing and Education Systems from a State of Emergency - Thompson, Shirley; Odejinmi, Mojibade; Hill, Stewart; Wastesicoot, Darryl (Canadian Planning and Policy / Aménagement et politique au Canada)

(untitled) (Association of Canadian University Planning Programs, 2026)
Housing and education systems on First Nation reserves are underfunded, inadequate and unsuitable due to colonial policy in Canada. A community-university partnership undertook participatory research with the York Factory First Nation (YFFN) to bring education home to their community at York Landing. This partnership successfully wrote funding proposals that established a state-of-the-art regional trades learning hub, Wikiwin Polytechnic Institute, with an “earn & learn” program for 20 students in partnership with the University of Manitoba. To measure the impact of Wikiwin, a longitudinal survey was conducted from 2023 to 2025 with the Wikiwin student cohort (n=17/20, 85% return rate), analyzed by between-group ANCOVA against a YFFN control group (n=9/20, 45% return rate). A statistically significant (p<0.05) improvement occurred in the Wikiwin student cohort compared to the control group across many social, human, and financial aspects. All Wikiwin students passed university courses and were fully employed with York Landing’s home construction. The Medicine Wheel framework analysis suggested that community-led education transformed the local housing and education systems. YFFN hopes to scale up Wikiwin to the provincial level to eliminate the education and employment gap, which is a Truth and Reconciliation call to action.